(untitled) (Global Journal of Computer Science and Technology, 2019)
The research explained the reason why we need personal cloud storage. This research will show steps on how to build a personal cloud storage by using credit card size Raspberry Pi (minicomputer), which will help the user to enable cloud storage mode to their external hard drive. However, other cloud storage services like Dropbox, Google Drive, and iCloud gives limited amount of storage. This research will help the users to use (1TB) or above size external hard drive to be use and have access anywhere from any device over internet. Also the second part of this research focus on replace the laptops to raspberry pi that lecturers use in the classroom to play PowerPoint slides, and videos at university. Universities use laptops to plug and play their educational slides and videos. All these laptops price and maintenance cost lot to the university, if we look deeply just for play slides we do not have to buy a laptop which cost 300 and also the lecturer have to carry the laptops all the times from the faculty to classes, moreover most of the times the laptops are not available. Overcome above statement, all the laptops can be replaced to 201C;Raspberry Pi201D; which cost 35 and it does not need any maintenance.